2021
DOI: 10.1016/j.msard.2021.102799
|View full text |Cite
|
Sign up to set email alerts
|

Associations between fatigue impact and lifestyle factors in people with multiple sclerosis – The Danish MS hospitals rehabilitation study

Abstract: Background:The lack of medical treatment options to reduce fatigue in patients with multiple sclerosis (MS) emphasize the importance of identifying potential non-pharmacological modifiable factors, as this may help advance current treatment strategies. The aim of this study was to identify potential modifiable lifestyle factors as well as patient-and disease-related characteristics, that are associated with fatigue in a large sample of clinically well-characterized patients with MS.Methods: This study was a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The pooled overall effect size for early retirement was 17.2% (95% CI 14.6–20.2; I 2 = 99.13). In three (4.5%) studies from 2006, 2018, and 2021, the prevalence of early retirement was over 50% [ 74 , 122 , 174 ]. In the most recent studies, the subjects’ sample largely comprised patients who attended rehabilitation clinics or were of advanced age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled overall effect size for early retirement was 17.2% (95% CI 14.6–20.2; I 2 = 99.13). In three (4.5%) studies from 2006, 2018, and 2021, the prevalence of early retirement was over 50% [ 74 , 122 , 174 ]. In the most recent studies, the subjects’ sample largely comprised patients who attended rehabilitation clinics or were of advanced age.…”
Section: Resultsmentioning
confidence: 99%
“…32, 120, 122, 123], Denmark (four, 6.0%) [73][74][75][76], Australia (three, 4.5%) [108,109,175], Belgium (three, 4.5%) [35,79,80], Holland (three, 4.5%) [61,63,176], Italy (three, 4.5%) [111 -113], Ireland (two, 3.0%) [47,48], Spain (two, 3.0%) [8, 28], Sweden (two, 3.0%) [90,91], Switzerland (two, 3.0%) [66,67], Argentina (one, 1.5%) [46], Austria (one, 1.5%) [39], Brazil (one, 1.5%) [55], the Czech Republic (one, 1.5%) [40], France (one, 1.5%) [85], Greece (one, 1.5%) [41], Hungary (one, 1.5%) [42], Iran (one, 1.5%) [59], Israel (one, 1.5%) [49], Russia (one, 1.5%) [45], Norway (one, 1.5%) [65], and Portugal (one, 1.5%) [44]. One (1.5%) study was multinational [170].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Current smoking was independently associated with fatigue in the regression model in which disability pension, anxiety and depression was not included, but not when these variables were included. In a Danish study, the researchers examined the impact of different lifestyle factors on MS fatigue, including smoking, alcohol habits and physical activity (Johansson et al, 2021). They found that physical activity reduced the impact of fatigue, and that smoking had a negative effect, while alcohol intake was not associated with fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the MFIS is a three-factor composite scale evaluating and quantifying the trait level of experienced fatigue impact on physical (9 items), cognitive (10 items) and psychosocial functioning (2 items). The MFIS is an acknowledged outcome measure in clinical trials, and despite being widely used in the Danish MS community (Taul-Madsen et al, 2020;Johansson et al, 2021;Oervik et al, 2017;Riemenschneider et al, 2021;Callesen et al, 2020), the Danish translation of the questionnaire has not yet been validated. Moreover, previous validation studies of other translations of the MFIS scale have reached different conclusions regarding the validity of the MFIS.…”
Section: Introductionmentioning
confidence: 99%